Apoptosis as pathogenic mechanism of infection with vesicular stomatitis virus. Evidence in primary bovine fibroblast cultures. (2023)
To determine whether fibroblasts from Blanco Orejinegro cattle, exhibit any level of resistance to infection against vesicular stomatitis virus (VSV) serotypes Indiana (VSV-I) or New Jersey (VSV-NJ), 30 fibroblast cultures were phenotyped to evaluate their resistance/susceptibility. Thirty three % of Blanco Orejinegro fibroblast cultures were classified as very resistant, 50% as resistant, and 17% as susceptible to VSV-I infection, whereas 20% were classified as very resistant, 50% as resistant and 30% as susceptible to VSV-NJ infection. Therefore, there appears to be a large variation in phenotypic polymorphism among the fibroblasts to infection by VSV. To elucidate the mechanisms responsible for this diversity, we searched for a possible relationship between resistance/susceptibility and production of factors with antiviral activity; however fibroblasts did not secrete factors with antiviral activity. We examined also whether apoptosis where induced by infection and its correlation with the polymorphism of resistance/susceptibility to VSV. Using morphological analyses, hypoploidy measurements, and level of phosphatidyl serine expression, high levels of apoptosis were measured in VSV infected fibroblasts. However, no correlation exists between apoptosis and the category of resistance/susceptibility to infection, indicating that apoptosis is a pathogenic mechanism of VSV.